2018
DOI: 10.1016/j.chom.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Septins Recognize and Entrap Dividing Bacterial Cells for Delivery to Lysosomes

Abstract: SummaryThe cytoskeleton occupies a central role in cellular immunity by promoting bacterial sensing and antibacterial functions. Septins are cytoskeletal proteins implicated in various cellular processes, including cell division. Septins also assemble into cage-like structures that entrap cytosolic Shigella, yet how septins recognize bacteria is poorly understood. Here, we discover that septins are recruited to regions of micron-scale membrane curvature upon invasion and division by a variety of bacterial spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 43 publications
5
92
0
Order By: Relevance
“…It has been recognised for approximately 10 years that septin assembly is membrane facilitated (Tanaka‐Takiguchi, Kinoshita, & Takiguchi, ), and recent work suggested that septins sense micron‐scale curvature at the plasma membrane (Bridges, Jentzsch, Oakes, Occhipinti, & Gladfelter, ). In agreement with this, a recent study showed that septins are recruited to regions of micron‐scale curvature presented by dividing bacterial cells (Figure [S3]), and cardiolipin (a curvature‐specific phospholipid) promotes septin recruitment to these regions (Krokowski et al, ). Following pharmacological inhibition of bacterial cell division, septins are recruited to bacterial cell poles but fail to assemble into cages, indicating that bacterial cell growth is required for septin cage entrapment.…”
Section: Other Septin Roles In Cell‐autonomous Immunitysupporting
confidence: 69%
See 4 more Smart Citations
“…It has been recognised for approximately 10 years that septin assembly is membrane facilitated (Tanaka‐Takiguchi, Kinoshita, & Takiguchi, ), and recent work suggested that septins sense micron‐scale curvature at the plasma membrane (Bridges, Jentzsch, Oakes, Occhipinti, & Gladfelter, ). In agreement with this, a recent study showed that septins are recruited to regions of micron‐scale curvature presented by dividing bacterial cells (Figure [S3]), and cardiolipin (a curvature‐specific phospholipid) promotes septin recruitment to these regions (Krokowski et al, ). Following pharmacological inhibition of bacterial cell division, septins are recruited to bacterial cell poles but fail to assemble into cages, indicating that bacterial cell growth is required for septin cage entrapment.…”
Section: Other Septin Roles In Cell‐autonomous Immunitysupporting
confidence: 69%
“…Septin cage‐entrapped S. flexneri is shown as dashed white outline. Image adapted with permission from Krokowski et al ()…”
Section: Septins and Bacterial Entrymentioning
confidence: 99%
See 3 more Smart Citations